Crystallization and Applications - Ben Smida, Youssef; Marzouki, Riadh (IntechOpen, 2022)
The crystallization process may be used in chemistry, physics, or materials science to prepare materials for special applications such as batteries, fuel cells, and optics. In chemistry and physics, researchers prepare polycrystalline powders or thin films. In biology and pharmacology, proteins and drugs are obtained as polycrystalline powder and their structures are determined by X-ray powder diffraction or neutron diffraction. The synthesis of polycrystalline powder or thin films depends on several factors such as temperature, pressure, and operating parameters. This book discusses the phenomenon of crystallization in several fields and applications.